2022
DOI: 10.3389/fnut.2022.845086
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in Fecal Metabolite Profiles Associated With Ramadan Fasting Among Chinese and Pakistani Individuals

Abstract: The human gut microbiota has been proposed to serve as a multifunctional organ in host metabolism, contributing effects to nutrient acquisition, immune response, and digestive health. Fasting during Ramadan may alter the composition of gut microbiota through changes in dietary behavior, which ultimately affects the contents of various metabolites in the gut. Here, we used liquid chromatography–mass spectrometry-based metabolomics to investigate the composition of fecal metabolites in Chinese and Pakistani indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 61 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Chen et al 53 used liquid chromatography-mass spectrometry-based metabolomics to investigate the composition of fecal metabolites in Chinese and Pakistani individuals before and after RF. Principal component analysis showed a distinct separation of metabolite profiles among ethnic groups and between pre- and post-fasting samples.…”
Section: Resultsmentioning
confidence: 99%
“…Chen et al 53 used liquid chromatography-mass spectrometry-based metabolomics to investigate the composition of fecal metabolites in Chinese and Pakistani individuals before and after RF. Principal component analysis showed a distinct separation of metabolite profiles among ethnic groups and between pre- and post-fasting samples.…”
Section: Resultsmentioning
confidence: 99%
“…According to a quick, non-systematic literature search in PubMed, at least two studies have been published since. One is a study by Chen et al ( 47 ), which is continuation to the study by Ali et al ( 29 ) and focuses on analyzing fecal metabolites. The second new study is the TRF study by Khan et al ( 7 ), which was briefly referenced in the introduction and the discussion.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of Ramadan fasting on gut microbiota were recently demonstrated by Chen et al (131). The authors investigated the influence of fasting during Ramadan on the gut metabolic profiles in fecal samples obtained from healthy Chinese (n = 16) and Pakistani (n = 18) subjects, using liquid chromatography-mass spectrometry-based metabolomics analysis (131).…”
Section: The Gut Microbiomementioning
confidence: 99%
“…The authors investigated the influence of fasting during Ramadan on the gut metabolic profiles in fecal samples obtained from healthy Chinese ( n = 16) and Pakistani ( n = 18) subjects, using liquid chromatography-mass spectrometry-based metabolomics analysis ( 131 ). Chen et al ( 131 ) concluded fasting leads to changes in metabolite profiles specific to each ethnic group in a manner dependent on dietary components. Additionally, these changes are correlated with dynamic shifts in microbiota composition and diversity which, in conjunction with dietary changes during Ramadan fasting, lead to the enrichment or depletion of various functional metabolites ( 131 ).…”
Section: Religious Fasting Nutrition and Individual Healthmentioning
confidence: 99%
See 1 more Smart Citation